Effect of Me2SO Cryoprotectant on the Activity of Reductive-Oxidative Enzymes in Placenta Tissue - Yurchenko, T. N.; Belonozhko, A. P.; Zhulikova, E. P.; Sharlay, T. M.; Strona, V. I.; Shepitko, V. I. (Problems of Cryobiology and Cryomedicine, 2003)
Using the methods of quantitative histochemistry and quantitative photometric analysis there was performed the investigation of the change in SDG, LDG, a-GPhDG, NAD.H2Â and NADP.H2Â activity in placenta tissue after its incubation with Me2SO cryoprotectant solution.